IMMOBILIZATION OF LEVANSUCRASE: STRATEGIES AND BIOTECHNOLOGICAL APPLICATIONS - bersaneti, Gabrielly Terassi; Baldo, Cristiani; Colabone Celligoi, Maria Antonia Pedrine (Journal of the Chilean Chemical Society, 2019)
Immobilization is an excellent tool for enzymatic stabilization, improving the biocatalytic processes, allowing the reuse of the enzyme and promoting an easier separation of the molecule of interest. Currently, new enzymatic bonding processes are arising on solid supports, based on classical immobilization methods. Amongst the supports used, chitosan is a polysaccharide that offers a unique set of characteristics, as biocompatibility, biodegradability, non-toxicity and antibacterial properties. Thus, many enzymes has being immobilized on this support, including levansucrase, that is able to synthesize levan and fructooligosaccharides, two important biomolecules which have beneficial health properties. These review present different methods of immobilization (physical adsorption, entrapment, crosslinking and covalent bonding) for fructosyltransferases, as well as different immobilization matrices that can be applied in biotechnological processes. However, studies are still needed in order to adopt efficient immobilization techniques, in which the biocatalyst remains more stable, in order to become the process attractive to the industrial sector.